Clinical Implementation of DPYD Pharmacogenetic Testing to Prevent Early-Onset Fluoropyrimidine-Related Toxicity in Cancer Patients in Switzerland - Begré, Ursina B. M.; Jörger, Markus; Aebi, Stefan; Amstutz, Ursula; Largiadèr, Carlo R. (Frontiers in Pharmacology, 2022)
The implementation of pharmacogenetic testing into clinical practice has been a slow process so far. Here, we review the implementation of pre-treatment testing of dihydropyrimidine dehydrogenase gene (DPYD) risk variants to prevent early-onset fluoropyrimidine (FP)-related toxicity in cancer patients in Switzerland based on data of a large Swiss diagnostic center. In January 2017, the Swiss Federal Office of Public Health introduced the reimbursement of DPYD testing by the compulsory health insurance in Switzerland based on evidence for the clinical relevance of DPYD-risk variants and the cost-effectiveness of pre-treatment testing, and on the availability of international guidelines. However, we did not observe a strong increase in DPYD testing at our diagnostic center from 2017 to 2019. Only a low number of DPYD- testing requests (28-42 per year), concerning mostly retrospective investigations of suspected FP-toxicity, were received. In contrast, we observed a 14-fold increase in DPYD testing together with a strong shift from retrospective to pre-treatment test requests upon the release of recommendations for DPYD testing prior to FP-treatment in April 2020 by the European Medicines Agency. This increase was mainly driven by three geographic regions of Switzerland, where partner institutions of previous research collaborations regarding FP-related toxicity are located and who acted as early-adopting institutions of DPYD testing. Our data suggest the important role of early adopters as accelerators of clinical implementation of pharmacogenetic testing by introducing these policies to their working environment and educating health workers from their own and nearby institutions.